2012
DOI: 10.4161/hv.20579
|View full text |Cite
|
Sign up to set email alerts
|

The detailed analysis of the changes of murine dendritic cells (DCs) induced by thymic peptide

Abstract: The aim of present research is to analyze the detailed changes of dendritic cells (DCs) induced by pidotimod(PTD). These impacts on DCs of both bone marrow derived DCs and established DC2.4 cell line were assessed with use of conventional scanning electron microscopy (SEM), flow cytometry (FCM), transmission electron microscopy (TEM), cytochemistry assay FITC-dextran, bio-assay and enzyme linked immunosorbent assay (ELISA). We demonstrated the ability of PTD to induce DC phynotypic and functional maturation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…During infancy, and in response to allergens, atopy-related type 2 T-helper cells (Th2) responses predominate [37,38]. Exposure to microbiota or immunomodulatory compounds can shift the balance from an atopic Th2 response to a nonatopic type 1 (Th1) response via the activation of DCs and subsequent regulatory T-cell activity [ 35,39,40,41,42,43].…”
Section: The Gut-lung Immune Axis: Infection and Inflammationmentioning
confidence: 99%
“…During infancy, and in response to allergens, atopy-related type 2 T-helper cells (Th2) responses predominate [37,38]. Exposure to microbiota or immunomodulatory compounds can shift the balance from an atopic Th2 response to a nonatopic type 1 (Th1) response via the activation of DCs and subsequent regulatory T-cell activity [ 35,39,40,41,42,43].…”
Section: The Gut-lung Immune Axis: Infection and Inflammationmentioning
confidence: 99%
“…Briefly, BV2 cells and primary microglial cells were suspended in culture medium, adjusted to a concentration of 1 9 10 6 -5 9 10 6 cells/mL, plated (2 mL/well) in 6-well cell culture plates, and incubated for 24 h. The cells were randomly assigned to four groups: negative control group, control group, Y27632 (10 lmol/L) group, and fasudil (41 lmol/L) group. The cells in the control, Y27632, and fasudil groups were incubated for 1 h at 37°C with FITCdextran (0.1 mg/mL, molecular weight, 40,000, FD-40s; Sigma) [22,23]. The negative control group was incubated with FITC-dextran at 4°C for 1 h to exclude extracellular binding of FITC-dextran, and was used to set the baseline value in flow cytometry.…”
Section: Fitc-dextran Uptake Analysis By Flow Cytometrymentioning
confidence: 99%
“…Up to now, clinical studies on this dipeptide have focused on its use as a treatment for respiratory tract infections in children (11,12). Previous studies have demonstrated that pidotimod modulates airway epithelial cell functions (13), enhances natural killer cell activity (14) and induces dendritic cell maturation (15). However, the impact of pidotimod on the regulation of allergic pulmonary inflammation is still not clear.…”
Section: Introductionmentioning
confidence: 99%